AL-LAQIT: HAK-HAK ANAK PUNGUT DI BAWAH UNDANG-UNDANG ISLAM DAN UNDANG-UNDANG SIVIL DI MALAYSIA: Al-Laqīṭ: The Rights of the Foundlings under Islamic and Civil Law in Malaysia - Noor, Zanariah (Jurnal Syariah, 2019)
The basis of the discussion in this article is the protection of the abandoned children or foundlings (al-laqīṭ ) that covered aspects namely custody, maintenance as well as self-identity. The discussion of foundling’s identity is related to his/her status as a free person (not slave), religion and lineage are based on Islamic principle that had been examined by distinctive jurists from different school of jurisprudences. This study utilized document analysis approach, scrutinizing Islamic jurists’ views as well as Malaysian law provisions on these issues. In Malaysia, aspects of custody, maintenance, and identity of the foundlings are handled differently from Islamic law pertaining to these issues, because matters related to the foundlings are under civil law jurisdiction, for instance, Child Act 2001 and Registration of Births and Deaths Act 1957, and the first institution that deals with the foundlings is the Department of Social Welfare. The law provisions under Acts/ Enactments of Islamic Family Law in Malaysia in relation to the foundlings are only relevant when the foundlings are adopted by the Muslim adoptive parents.